Bioprospecting Antarctic microalgae as anticancer agent against PC-3 and AGS cell lines - Inan, Benan; Mutlu, Betul; Karaca, Guelcan Aysin; Koc, Rabia Cakir; Ozcimen, Didem (ELSEVIER, 2023)
Studies on pharmaceutical and medicine applications of cold adapted polar microalgae are very limited. In this study, it is aimed to evaluate the cytotoxic activity of polar microalgae extracts against different cancer cell lines. In this context, the cultivation of Chlorella variabilis YTU.ANTARCTIC.001 and Auxenochlorella pyrenoidosa OZCIMEN.001 were carried out and their oil extracts were encapsulated in nanoparticle to preserve its bioactive components against oxidation and to increase the penetration of the extract into the cancer cells. To investigate the anticancer effects of microalgae, cell culture studies were performed and then the extracts and nanoparticles were applied to the AGS and PC-3 cell lines via XTT method. In line with the study, it was observed that C. pyrenoidosa extracts showed higher cytotoxicity than C. variabilis against AGS and PC-3 cells. At 500 & mu;g/ml, AGS cells tested with C. variabilis showed a decrease down to 58 % and at the same concentration of C. pyrenoidosa, it was determined as 51 %. As for nanoparticle form, C. variabilis extracts exhibited higher cytotoxic activity and better anticancer properties. It was found that, these potential anticancer effects appeared to be largely concentration-dependent. Moreover, C. variabilis extract was determined as less effective on scratch closure than C. pyrenoidosa. In conclusion, the obtained data will pave the way to produce biotechnological drugs based on polar microalgae.
Keywords: Antarctic microalgae; Microalgae oil; Anticancer activity; Encapsulation; Nanoparticle; FRESH-WATER MICROALGA; ETHANOL EXTRACT; OIL; INFLAMMATION; ANTIOXIDANT; FIBERS; Biotechnology & Applied Microbiology; Engineering